Propaganda and international relations: an outlook in wartime - Marsili, M. (2016)
The article is a little research, carried out in the seminars of International Relations of the Ph.D. program in History, Studies of Security and Defense. The aim of the work is to highlight the role of propaganda during the conflicts in the contemporary age, particularly during the two World Wars. The propaganda developed during two major conflicts of the '900 as a 'true weapon' and instrument of government policy in international relations, has perfected the techniques of 'news management', and today is a real and relished 'art' applied to guide public opinion in favor of government decisions.